FORMATION OF SOYBEAN PRODUCTIVITY DEPENDING ON SOWING TIME AND PLANT GROWTH REGULATORS - Shepilova, T. P.; Petrenko, D. I.; Leshchenko, S. M.; Artemenko, D. Yu. (Scientific Progress & Innovations, 2021)
The increase in soybean production is explained by a significant demand for soya products in many countries. It is possible to realize the genetic potential of modern soybean varieties by studying the issues of varietal growing techniques. An important factor is the sowing time of soybean. It depends on seeds’ germinating capacity, the simultaneity of plants’ appearance, the conditions of their further growth caused by lighting, water consumption, temperature and other factors that determine crop productivity. The use of growth regulators helps to increase the plant resistance to adverse and changing environmental factors, improves the development of the root system and plant nutrition. The purpose of the research was to identify the influence of sowing time and seed treatment with growth regulators on the productivity of Romashka mid-ripening soybean variety in the Northern Steppe of Ukraine. The task was to determine the influence of sowing dates and growth regulators on seed germinating capacity, leaf- area duration, number of tubercles, formation of yield structure elements. Field research was conducted during 2019–2021 and the experiment was established by the method of split sites. According to the study results, it was found that Dominant growth regulator had a significant impact on seed germination when at sowing on April 20, seed germinating capacity made 84.2 %, that is 3.6% increase in comparison with the control. When sown on May 1, the germinating capacity was higher and amounted to 85.5 %. The largest leaf- area duration of plants and the number of tubercles was formed at seed treatment with Dominant growth regulator at sowing on April 20 – 1,037 cm2/plant, and 31.2 pcs/plant, which is by 8.5 % and 9.1 % higher than in the control. The transfer of sowing time from the first to the second term resulted in a decrease in the leaf- area duration of one plant by 45 cm2 on the average, which made 4.5 %. At the first term, soybean plants showed better yield structure indicators. When applying Dominant, the largest number of beans was formed – 25.4 pcs/plant, and seed weight was 5.03 g/plant, which exceeded the control variant by 7.2 and 5.0%, respectively. The highest yield of Romashka mid-ripening variety – 2.06 t/ha was obtained at the first sowing period, on April 20. The postponement of the sowing time to May 1 caused the yield decrease by 0.18 t/ha, or 8.7 %, on the average. Dominant complex preparation turned out to be more effective than other growth regulators, ensuring the highest soybean yields at early sowing – 2.17 t/ha and the yield increase of 0.21 t/ha (10.7 %).